Bibliometric and visual analysis of transcranial direct current stimulation in the web of science database from 2000 to 2022 via CiteSpace - Sun, Weiming; Song, JingJing; Dong, Xiangli; Kang, Xizhen; He, Binjun; Zhao, Wentao; Li, Zhaoting; Feng, Zhen; Chen, Xiuping (Frontiers in Human Neuroscience, 2022)
Objective: This study aimed to evaluate the current research hotspots and development tendency of Transcranial Direct Current Stimulation(tDCS) in the field of neurobiology from a bibliometric perspective by providing visualized information to scientists and clinicians. Methods: Publications related to tDCS published between 2000 and 2022 were retrieved from the Web of Science Core Collection (WOSCC) on May 5, 2022. Bibliometric features including the number of publications and citations, citation frequency, H-index, journal’s impact factors and journal citation reports were summarized using Microsoft Office Excel. Co-authorship, citation, co-citation, and co-occurrence analyses between countries, institutions, journals, authors, references and keywords were analyzed and visualized using CiteSpace (version 6.1.R3). Results: A total of 4756 publications on tDCS fulfilled the criteria we selected and then were extracted from the WoS. The United States (1190 publications, 25.02%) and Harvard University (185 publications, 3.89%) were the leading contributors among all the countries and institutions, respectively. Nitsche MA and Fregni F, the key researchers, made great achievements in tDCS. Brain Stimulation (306 publications) had the highest number of publications relevant to tDCS, and the highest citations (4,042 times). In terms of potential hotspots, we learn through reference co-citation analysis timeline viewer related to tDCS that “depression”#0, “Sensorimotor network”#10, “working memory”#11, “Transcranial magnetic stimulation”#9 might be the future research hotspots, while keywords with the strong burst and still ongoing were “intensity”(2018-2022), “impairment”(2020-2022), “efficacy”(2020-2022) and “guideline”(2020-2022). Conclusions: This was the first-ever study of peer-reviewed publications relative to tDCS using several scientometric and visual analytic methods to quantitatively and qualitatively reveal the current research status and trends in the field of tDCS. Through the bibliometric method, we gained an in-depth understanding of the current research status and development trend on tDCS. Our research and analysis results may provide some practical sources for academic scholars and clinicians.